# How do you use the limit definition to find the derivative of #f(x)=sqrt(3-2x)#?

You can now use substitution to evaluate.

If you were to check this using the chain rule, you would get the same result.

Hopefully this helps!

By signing up, you agree to our Terms of Service and Privacy Policy

To find the derivative of ( f(x) = \sqrt{3 - 2x} ) using the limit definition:

- Begin with the function ( f(x) = \sqrt{3 - 2x} ).
- Use the definition of the derivative: [ f'(x) = \lim_{h \to 0} \frac{f(x + h) - f(x)}{h} ]
- Substitute ( f(x) = \sqrt{3 - 2x} ) into the definition.
- Simplify the expression ( f(x + h) - f(x) ).
- Divide the expression by ( h ).
- Take the limit as ( h ) approaches 0 to find the derivative.

By signing up, you agree to our Terms of Service and Privacy Policy

- How do you find the instantaneous rate of change for #f(x) = x^2 + 3x + 4# for x=2?
- How do you find the equation of a line tangent to the function #y=x^3-x# at (-1,0)?
- How do you use the limit definition to find the slope of the tangent line to the graph #f(x)= 2x²-3x-5# at x=2?
- Differentiate #cos(x^2+1)# using first principle of derivative?
- What is the equation of the line normal to #f(x)=(5+4x)^2 # at #x=7#?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7